Potential of kerosene-diesel blends as alternative fuels for diesel engines: Perspectives from spray combustion characteristics. (1st March 2023) - Wang, Zhaowen; Li, Xiaojie; Xiang, Lin; Huang, Yuhan; Lang, Bing; Cheng, Xiaobei; Zhang, Jie
Graphical abstract: Highlights: Spray, combustion and soot characteristics were studied by combining various optical methods. Higher kerosene ratio enhances spray evaporation and reduces wall impingement in engines. Higher kerosene ratio increases both ignition delay and flame lift-off length. Kerosene component reduces soot formation. 25% blending ratio of kerosene is the optimal for real engine applications. Abstract: To explore the application potential of kerosene (RP-3)/diesel blends as alternative fuels for diesel engines, the spray combustion characteristics of neat diesel, neat RP-3 and RP-3/diesel blends (varied from 25 % to 75 % of RP-3) were systematically compared in an optical constant volume combustion chamber under non-evaporating (0 % O2, 293 K), evaporating (0 % O2, 900 K) and combustion (21 % O2, 900 K) conditions. Their spray, evaporation, combustion and soot emission characteristics were visualized using various high-speed imaging techniques. The results show that RP-3/diesel blending ratio has significant effects on the spray and combustion processes. Under non-evaporating condition, higher RP-3 contents slightly decrease the spray penetration but increase the corresponding spray angle and volume. Under evaporating condition, the spray angle and volume follow the similar trend as those under non-evaporating condition except for slight fluctuations, but the liquid length decreases with the increase of blending ratio. Unexpectedly, the vapor penetrations of neat diesel and RP-3 are similar and longer than those of their blends. Under combustion condition, both the ignition delay and flame lift-off length increase with the RP-3 blending ratio. In addition, RP-3 component reduced the peak soot mass by 9.78 %, 14.7 % and 17.56 % for R25, R50 and R75, respectively. In summary, this study suggests that RP-3/diesel blends are suitable alternative fuels for diesel engines, in terms of faster evaporation and lower soot emissions. We recommend a blending ratio of 25 % as the most promising fuel for further investigations in real engines.